The Swiss National MD-PhD Grants Programme: an analysis of the career trajectories of grant recipients between 1992 and 2021 - Myriam Tapernoux; Sarah Vermij; Gaudenz Metzger; Hanns Ulrich Zeilhofer (Swiss Medical Weekly, 2024)
AIM OF THE STUDY: The aim of this study is to provide an analysis of the career trajectory of the recipients of a Swiss National MD-PhD grant thirty years after the creation of the Swiss interuniversity MD-PhD programme.